Peran Guru PAK Dalam Meningkatkan Minat Belajar Peserta Didik Dengan Metode Gerak Lokomotor - Yupriskila Dwi Hadassah; Sandra Rosiana Tapilaha (Sepakat : Jurnal Pastoral Kateketik, 2023)
Education is increasingly advanced and even varied, and so should Christian Religious Education teachers. Christian Religious Education teachers are required to be creative in educating and creating a lively classroom atmosphere. The influence of the teacher in the classroom is very important. The method used in this writing is descriptive qualitative method so that the results of the research can be developed further. Christian Religious Education is an education that is carried out to bring students to Christ, because the main center of Christian Religious Education learning is Christ. The purpose of writing this article is to provide an understanding for Christian Religious Education teachers that in the learning process they can use the locomotor movement method, so that students are not bored with monotonous learning. The role of Christian religious education teachers in increasing students' interest in learning with the locomotor method is very important. Locomotor movements are an important part of physical education and sports programs, and the development of locomotor movements also helps learners acquire the basic motor skills needed to live healthy and physically active lives.